The impact of transparent packaging: how transparent packaging for organic foods affects tourists' green purchasing behavior - Kuang, TingYue; Yang, Dajun; Zou, Dingxia (Frontiers in Nutrition, 2024)
Previous studies have shown that transparent packaging can influence consumer behavior, but the impact on tourists' environmentally friendly purchase intentions is not well-understood. This study conducted four experiments with 1,513 participants to explore the role of transparent packaging in tourists' willingness to engage in green purchasing. Factors such as ecological concern, nature connectedness, and environmental consequences were also examined. The results showed that transparent packaging significantly enhanced tourists' purchase intentions and that ecological concern, nature connectedness, and environmental consequences had a significant influence on these intentions. These findings contribute to understanding the packaging paradox and its relationship with tourists' green purchasing behavior. The study has implications for the food retail industry and the promotion of sustainable development in scenic areas, suggesting that transparent packaging can effectively enhance tourists' purchase intentions for green products. Understanding factors like ecological concern and nature connectedness can also provide valuable insights for the industry to improve marketing strategies and promote environmentally friendly choices among tourists.